The Relationship Between Cognitive Dysfunction Through THINC-Integrated Tool (THINC-it) and Psychosocial Function in Chinese Patients With Major Depressive Disorder - Han, Han; Hou, Yanyan; Yao, Shuqiao; Hu, Shaohua; Zhou, Qi; Yu, Xin; McIntyre, Roger S.; Shi, Chuan (Frontiers in Psychiatry, 2021)
Background: Herein, we validate the psychometric properties of the Chinese version of the THINC-integrated tool (THINC-it) as a screening tool for cognitive deficits in patients with major depressive disorder. The primary aim of this study to determine whether cognitive deficits as detected by the THINC-it tool in adults with major depressive disorder (MDD) are associated with workplace productivity and/or psychosocial function. Methods: Subjects aged 18-65 (n=91) with MDD were evaluated and compared to age- and sex- matched healthy controls (n=95). Completed the THINC-it tool. The THINC-it tool, as well as the paper version of the Perceived Deficits Questionnaire for Depression-5-item (PDQ-5-D), Sheehan Disability Scale (SDS), The Work Productivity and Activity Impairment questionnaire- Specific Health Problem (WPAI-SHP). Results: There were significant differences in THINC-it scores (p<0.01), the average of HAMD total score (p<0.01) and all aspects of SDS (p<0.01) between two groups. There were significant differences in the four aspects of WPAI between the two groups in the employed status(p<0.01). THINC-it subjective cognition and SDS total score, SDS work/school, SDS social, SDS family showed significantly correlation (r ranging from 0.255 to 0.386, p<0.01). SDS and THINC-it Objective cognition, THINC-it comprehensive cognition were no correlation between two groups. HAMD total score and SDS total score, SDS social, SDS family showed significantly correlation (r ranging from 0.208 to 0.220 p<0.01). Pearson correlation coefficient between cognitive function and work productivity in MDD showed that THINC-it subjective cognition were correlated with the presenteeism, work productivity loss and overall activity impairment of WPAI (r ranging from 0.394 to 0.468 p<0.01). There was no correlation between THINC-it objective cognition and all tests of WPAI (p>0.05). Conclusion: The Chinese version of THINC-it can be used to assess the overall cognitive function of patients with MDD. The subjective cognitive function measured by THINC-it is significantly correlation with the impairment of psychosocial function. Keywords: THINC-it, MDD, Cognitive function, psychosocial function, work productivity